2010
DOI: 10.14742/ajet.1091
|View full text |Cite
|
Sign up to set email alerts
|

Using blogs to help language students to develop reflective learning strategies: Towards a pedagogical framework

Abstract: Due to the social changes brought about in no small part by Web 2.0 tools, the potential impact of the blog writing phenomenon upon teaching and learning contexts reveals an important area for consideration for all university educators, and in particular for e-learning practitioners. Today, web users may access a wide variety of media to express themselves and to communicate with others. These may include conventional blog websites such as blogger.com or indeed social networking sites such as MySpace, Facebook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 26 publications
3
44
0
Order By: Relevance
“…These comments contradicts [15] statement that blog's "underdetermined" design, where the system is engaging, yet intuitive and easy to learn makes it equitable for many age groups and both genders. However the results of this study align positively with [16] who mention that the basic mechanics of blogging was a challenge for students in their research as well. Some preferred traditional pen and paper environment compared to the online learning.…”
Section: B Familiarity With Technology and Internet Connectivitysupporting
confidence: 84%
“…These comments contradicts [15] statement that blog's "underdetermined" design, where the system is engaging, yet intuitive and easy to learn makes it equitable for many age groups and both genders. However the results of this study align positively with [16] who mention that the basic mechanics of blogging was a challenge for students in their research as well. Some preferred traditional pen and paper environment compared to the online learning.…”
Section: B Familiarity With Technology and Internet Connectivitysupporting
confidence: 84%
“…Some scholars indicated that blogging enables students to achieve a range of cognitive and social learning outcomes, as well as to develop reflective learning strategies (Birch & Volkov, 2007;Hourigan & Murray, 2010;Tan, Ladyshewsky & Gardner, 2010). Alm (2009) also concluded that blogging can positively affect learners' willingness to communicate by providing them with a personal space where they feel safe to express themselves and to interact with others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They are now a well-established and widely recognised form of digital communication and should thus be taken seriously in educational settings (Davies & Merchant, 2009). There is a growing body of scholarly work on the application of blogs in various academic disciplines such as teacher education (Deng & Yuen, 2011;Hernández-Ramos, 2004;Hourigan & Murray, 2010;Ray & Coulter, 2008;Stiler & Philleo, 2003;Wopereis, Sloep & Poortman, 2010;Yang, 2009), business (Williams & Jacobs, 2004), and language learning (Ducate & Lomicka, 2008;Mompean, 2010). Blogging is acclaimed as a flexible tool that can be used to support both individual and community learning.…”
Section: Introductionmentioning
confidence: 99%